Sociodemographic Factors and Resilience in Directors of Public Educational Institutions of the Peru - Del Águila Chávez, Mónica Rocío (2023)
Summary The general objective of this research was to determine the sociodemographic factors related with resilience in public school authorities in Peru. The design used was the no experimental, transversal, and no causal correlational. The sample consisted of 1061 authorities (school principals and deputy directors) of public schools in Peru. The sampling was non-probabilistic for convenience. The instruments used were a sociodemographic survey designed for this research and the “Escala de Resiliencia Docente”, for which evidence of validity and reliability was determined. The results indicated that the sociodemographic variables related with resilience were female sex (OR = 1.59 [95% CI = 1.13-2.23]; X2 = 6.666: p